GAMBARAN PENGGUNAAN ANALGETIK PADA PASIEN RAWATAN INTENSIF DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI-DESEMBER 2015 - Ramadani, Latifah; Hidayat, Nopian (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTPatients in the ICU generally experience pain complaints due to various conditions, diseases and various medical actions obtained. Pharmacological therapy given to patients with pain complaints in the ICU is analgetic. The purpose of this study was to find out how the description of the use of analgetic for patients in ICU RSUD Arifin Achmad in the period of January-December 2015. This study was a retrospective descriptive study using secondary data from medical records. There were 151 samples. Characteristics of patients treated in the ICU showed that the number of female patients was higher than male patients (52.3%). The largest age group admitted to the ICU was 46-55 years (22.5%). The most widely used financing status is JKN (67.5%). The most diagnosis in patient in ICU is postoperative (61.59%). Percentage of analgetic usage was 72,85%. The most common analgetic groups were NSAIDs (61.54%), which are paracetamol (26.92%), and ketorolac (24.36%). Patients in ICU was given the therapeutic dose (100%). The highest degree of pain in patients in ICU was moderate pain (64.47%)..Keywords : Pain,analgetic, ICU, dosage